Experimentation and analysis of powder injection molded Ti10Nb10Zr alloy: a promising candidate for electrochemical and biomedical application - GÜLSOY, HAMİT ÖZKAN; GÜLSOY, NAGİHAN; MUTLU, ÖZAL (ELSEVIER, 2019)
This paper describes the microstructural, mechanical and corrosion properties of injection molded Ti10Nb10Zr alloys. T10Nb10Zr powder was injection molded with wax-based binder. The critical powder loading for injection molding was 55 vol% for feedstock. Binder debinding was performed in solvent and thermal method. After debinding the samples were sintered at different temperatures and times in vacuum atmosphere (10-5 mbar) to obtain fully dense parts. Metallographic studies were conducted to determine the extent of densification and the corresponding microstructural changes. The electrochemical property and biocompatibility of the sintered samples were performed electrochemically, by selfbody -fluid immersion tests and cell culture experiments. The results show that Ti10Nb10Zr alloys could be sintered to a maximum 99% of theoretical density. Maximum ultimate tensile strength, elongation and hardness obtained were 748 MPa, 14.3 and 114 HRB respectively at 1500 degrees C for 3 h. Additionally, the sintered i10Nb10Zr alloys exhibited high mechanical and corrosion properties in a physiological environment. (C) 2019 The Author. Published by Elsevier B.V.
Keywords: Powder injection molding; Titanium alloy; Sintering; Mechanical properties; Biocompatible; MECHANICAL-PROPERTIES; CORROSION BEHAVIOR; TITANIUM IMPLANTS; TI ALLOY; BIOCOMPATIBILITY; MICROSTRUCTURE; PARAMETERS; SURFACE